A dynamic prediction method for maize ear yield by fusing morphological and kinetic features - Li Tan; Qiankun Fu; Fan Zhang; Jun Fu; Fengxin Yan; Naimov Alisher (Biosystems Engineering, 2026)

Engineered small extracellular vesicles–integrated multifunctional hydrogel reprograms the wound immune microenvironment for accelerated skin repair - Zhong Liu; Xinyu Zhu; Jun Cheng; Kewei Li; Yang Lou; Xiaopeng Sun; Yuhong Fan; Min Wang; Hui Qian; Yanbin Liu; Hua Ding; Song Guo; et al. (Chemical Engineering Journal, 2026)

Tuning the signal-to-noise ratio: An electrokinetic strategy for high-fidelity SERS biosensing of microRNA-21 - Kangzhe Cao; Fan Zhang; Jiakun Zhang; Jinjin Fu; Ping Lu; Jun-Tao Cao; Huiqiao Liu (Analytica Chimica Acta, 2026)

Reactive oxygen species mediate autophagy in the regulation of ivermectin resistance in Haemonchus contortus - Huanhuan Zhang; Nana Fu; Xiutao Hu; Anben Li; Fan Zhang; Xiaonan Sun; Xuezhang Zhou; Jun Du; Yang Liu (Veterinary Parasitology, 2026)

Inorganic Ammonia carbon capture pilot testing and simulation research - Xia Zhonglin; Fan Shuaijun; Zuo Jiahai; Wang Xiaohua; Chen Wentong; Yang Fu; Jia Jun; Chen Luyao; Meng Weian; Zhao Zhenyang; Zhu Hongtao; Ma Xiaoying; et al. (Chemical Engineering Journal, 2026)

Rapid assembly of structurally diverse 3,4-dihydroquinazolines with anticancer activity via SDS-promoted aqueous synthesis - Fu-Qiang Yu; Pei-Lu Song; Yan-Rui Fan; Jun-Wei Wang; Xu-Jie Wang; Jin-Fei Yang (Molecular Diversity, 2026)

A coupled elastoplastic damage subloading surface model for rock-like geomaterials subjected to triaxial cyclic compression - Jun Wu; Wei Wang; Ya-jun Cao; Shi-fan Liu; Wan-qing Shen; Jian-fu Shao (Computers and Geotechnics, 2026)

Enhanced mechanical, thermal, and rheological properties of nanocellulose-reinforced multifunctional sanxan gum hydrogels - Yue Wang; Baoping Wang; Ping Cheng; Xue Zhang; Jun Han; Fang Tian; Lina Fu; Zhiping Fan (Food and Bioproducts Processing, 2026)

Modulating Ti-O-Bi-based charge transport channels across Bi6O7/Ti3C2Tx interface for augmented targeted iodide ion removal via capacitive deionization - Nan Feng; Xinping Fu; Mingxing Liang; Yuting Ning; Chenghao Li; Tongtao Fan; Huan Zhang; Wei Yao; Donghai Yuan; Jun Cui (Chemical Engineering Journal, 2026)

Oral delivery of colon targeted zein-xanthan gum nanoparticles loaded with giant salamander Maillard hydrolyzed peptide: improving ulcerative colitis by regulating the production of antioxidant peptides in digestive products - Jing-Jing Fu; Fan-Yu He; Yong-Jie Long; Wen-Qiang Cai; Jun-Xin Wu; Yue-Wen Chen (Food Bioscience, 2026)

Safety evaluation of pasteurized Akkermansia muciniphila YGMCC2645 - Jie Tian; Zhili He; Minlei Zhao; Xianghong Ke; Yinjing Zhang; Jingjing Qu; Ying Xia; Shaohua Fu; Wenxiang Yang; Lanjie Pei; Jun Fan; Jianguo Chen; et al. (Food and Chemical Toxicology, 2026)

Molecular identification and genetic diversity of Echinococcus granulosus sensu stricto in livestock from Qinghai lake on the Qinghai-Tibetan plateau - Jun He; Guoyan Zhou; Fan Zhang; Hongrun Ge; Ao Chen; Ru Meng; Zhihong Guo; Yijuan Ma; Yong Fu (Veterinary Research Communications, 2026)

Integrative transcriptomic and epigenomic analysis reveals the molecular mechanism of light-enhanced calcification in giant clams - Wenjie Yi; Fan Mao; Ke Wan; Shiwei Fu; Md. Abu Kawsar; Xiangcheng Yuan; Jun Li; Zhiming Xiang; Shu Xiao; Weihua Zhou; Ziniu Yu; Yang Zhang (Aquaculture, 2026)

The plant ontology of cell types - Hongyu Chen; Pu Liang; Xiaolin Lu; Shuai Jiang; Jingjing Jin; Jiaqi Cai; Yaqian Lu; Dihuai Zheng; Jie Yao; Qinjie Chu; Huixia Shou; Chengxin Fu; et al. (Molecular Plant, 2026)

Mitochondrial ORF188 confers salt stress tolerance in rapeseed via an ATP-dependent enhancement of antioxidant capacity - Shi-Hang Fan; Zi-Hong Huang; Jun Li; Xiang Ji; Wei Hua; Zheng-Wei Fu (Plant Cell Reports, 2026)

Genetic origins and climate‐induced erosion in economically important Asian walnuts - Peng‐Zhen Fan; Guang‐Fu Zhu; Moses C. Wambulwa; Richard I. Milne; Zeng‐Yuan Wu; Ya‐Huang Luo; Robabeh Shahi Shavvon; Alistair S. Jump; Debabrata Maity; Lian‐Ming Gao; Hai‐Ling Qi; Hong‐Yu Wu; et al. (Conservation Biology, 2026)
The global climate is undergoing unprecedented changes, posing significant threats to species persistence. However, the spatiotemporal impacts on genetic diversity remain poorly understood, hindering species conservation and management. Walnuts, generally referred to as Juglans regia and J. sigillata , are economically vital in Asia, but little is known about their genetic origins and how the species will be affected by future climate change. Using 31 microsatellites, we genotyped 5282 individuals from 233 populations of walnuts in Asia. We assessed genetic diversity patterns and demographic history and investigated potential future genetic erosion risks. Genetic diversity of walnuts was high in the Himalaya and Hengduan Mountains. The 2 species diverged during the Pleistocene (around 1.41 Ma BP), and J. regia contained 2 genetic groups (JR1 and JR2). The JR2 group had the lowest diversity and likely arrived in northern China around 9.77 ka BP, perhaps via human transport. The Western Himalaya likely served both as a glacial refugium and the center of origin for J. regia , and the Eastern Himalaya appears to have been the refugium for J. sigillata . The 2 species appear to have hybridized in the Central Himalaya and the Sichuan basin and surroundings, forming two distinct hybrid zones. Our results indicate that genetic diversity will be reduced by up to 9.03% due to range loss under future climate change and dramatic genetic structure turnover in the Himalaya and Hengduan Mountains. In situ conservation in the Himalaya is essential for safeguarding genetic diversity and adaptive potential in Asian walnuts, while ex situ preservation of genetically unique wild germplasm, coupled with its integration into breeding programs, will enhance climate resilience. The findings advance our understanding of the origin of Asian walnuts and how future climatic change may affect their genetic diversity, offering a model for conservation and breeding strategies in other tree species facing similar threats.

Single nucleotide polymorphisms of the Waxy gene and their relationship with the physicochemical properties of Pueraria lobata (kudzu) starch - Ruiqi Zha; Ying Fan; Yuhao Fu; Chunyan Liu; Haoliang Sun; Jiaxin Wan; Min Wei; Zhixing Jin; Peng Li; Zhongyan Zhu; Jing Wei; Jun Yin; et al. (Carbohydrate Polymers, 2025)

Singlet oxygen-driven non-radical oxidation of phenylurea herbicides in aqueous environment: Reaction behaviors and degradation mechanisms via unactivated PMS systems - Zi-Han Feng; Lin-Hao Xu; Fu-Xiang Tian; Fan Lai; Jing Ye; Yu-Qiong Gao; Dong-Su Bi; Xiao-Jun Hu (Journal of Water Process Engineering, 2025)

Enhancing the anti-inflammatory efficacy of polysaccharides through processing techniques: a case study on Atractylodes macrocephala - Hong-Da Xuan; Sheng-Nan Shen; Chun-Jin Fu; Jie Zhou; Rui-Xing Chen; Jun-Zhe Zhang; Xiao-Xia Liu; Feng-Qin Li; Yi-Fan Zhao; Dong Zhang; Hai-Ning Lyu; Fang Wang (Natural Product Research, 2025)

The importance of tropical tree-ring chronologies for global change research - Peter Groenendijk; Flurin Babst; Valerie Trouet; Ze-Xin Fan; Daniela Granato-Souza; Giuliano Maselli Locosselli; Mulugeta Mokria; Shankar Panthi; Nathsuda Pumijumnong; Abrham Abiyu; Rodolfo Acuña-Soto; Eduardo Adenesky-Filho; et al. (Quaternary Science Reviews, 2025)

Hybrid crosslinking cellulose nanofibers-reinforced zwitterionic poly (ionic liquid) organohydrogel with high-stretchable, anti-freezing, anti-drying as strain sensor application - Dong Fu; Linhui Xing; Yang Xie; Peng Li; Fan Yang; Xin Sui; Jiaying Liu; Jialong Chi; Bo Huang; Jun Shen (Carbohydrate Polymers, 2025)

Safety evaluation of alpha-glycerylphosphorylcholine as a novel food - Jie Tian; Xianghong Ke; Yinjing Zhang; Jingjing Qu; Shaohua Fu; Ying Xia; Wenxiang Yang; Yanhua Zeng; Jun Fan; Yanmei Li; Bolin Fan (Food and Chemical Toxicology, 2025)

Single-cell omics: experimental workflow, data analyses and applications - Fengying Sun; Haoyan Li; Dongqing Sun; Shaliu Fu; Lei Gu; Xin Shao; Qinqin Wang; Xin Dong; Bin Duan; Feiyang Xing; Jun Wu; Minmin Xiao; et al. (Science China Life Sciences, 2025)

Tower-based profiles of wintertime secondary organic aerosols in the urban boundary layer over Guangzhou - Yao Li; Hong Ren; Shengzhen Zhou; Chenglei Pei; Min Gao; Yuxuan Liang; Dian Ye; Xijing Sun; Fenghua Li; Jun Zhao; Jian Hang; Shaojia Fan; et al. (Science of The Total Environment, 2024)

Evaluation and comparison of iohexol elimination by UV/peroxymonosulfate and UV/persulfate processes: Radical roles, influence factors and iodinated trihalomethanes formation - Chen-Cheng Mo; Fu-Xiang Tian; Bin Xu; Fan Lai; Yu-Qiong Gao; Yan Ma; Zi-Han Feng; Zi-Jian Yao; Dong-Su Bi; Xiao-Jun Hu (Journal of Water Process Engineering, 2024)

Molecular characterization, spatio-temporal expression patterns of crtc2 gene and its immune roles in yellow catfish (Pelteobagrus fulvidraco) - Wan-Hong Zeng; Zheng-Yong Wen; Xiu-Ying Wei; Yu He; Luo Zhou; Peng Hu; Qing-Chao Shi; Chuan-Jie Qin; Jun Wang; Rui Li; Xiao-Ying Jing; Wei Hu; et al. (Fish & Shellfish Immunology, 2024)

Corrigendum to “Lubricating MXenzyme-based hybrid hydrogel reverses oxidative damage to alleviate osteoarthritis” [Chem. Eng. J. 482 (2024) 148815] - Zhao Zhang; Debin Cheng; Jingxin Pan; Dong Liu; Jun Fu; Hongbin Fan (Chemical Engineering Journal, 2024)

Effects of three different protein levels on the growth, gonad development, and physiological biochemistry of female Pengze crucian carp (Carassius auratus var. Pengze) broodstock - Jun Xiao; Fan Long; Liyun Ding; Yuan Yao; Weihua Wu; Yilong Fu; Wenjing Chen (Frontiers in Marine Science, 2024)
A 56-days feeding experiment was conducted to evaluate the effect of dietary protein levels on fish growth, gonad development, and physiological biochemistry of female Pengze crucian carp ( Carassius auratus var. Pengze) broodstock. Three isoenergetic diets were formulated, and the crude protein levels were 26.85%, 35.73% and 44.38%, the lipid levels were 7.39%, 7.92% and 7.91%, respectively. The results showed that the weight gain rate (WGR), the specific growth rate (SGR) and the protein efficiency ratio (PER) of the female Pengze crucian carp broodstock increased significantly and the feed conversion ratio (FCR) decreased significantly when the dietary protein level was 35.73% ( P < 0.05). The WGR, the SGR and the PER were significantly higher in the 35.73% and 44.38% protein groups than in the 26.85% protein group ( P <0.05). Increasing dietary protein levels led to a significant increase in the gonad index and the egg menstrual length of the female Pengze crucian carp broodstock ( P <0.05). The higher protein levels resulted in a significant increase in total amino acids, total essential amino acids, and total nonessential amino acids ( P <0.05). The varying ovaries of each group of total saturated fatty acids, total highly unsaturated fatty acids, and total polyunsaturated fatty acids all increased significantly with increasing protein levels ( P <0.05). Furthermore, the aspartate transaminase (AST), low-density lipoprotein cholesterol (LDLC), and malondialdehyde (MDA) contents in plasma were significantly lower in the 35.73% and 44.38% groups than in the 26.85% group ( P < 0.05). The 35.73% group exhibited the highest plasma superoxide dismutase (SOD) activity,. The plasma vitellogenin (VTG), estradiol 2 (E2), and progesterone (PROG) in plasma of female Pengze crucian carp broodstock were significantly higher in the 35.73% and 44.38% protein groups than in the 26.85% protein group ( P <0.05). The results showed that the addition of an appropriate amount of protein to the feed can significantly improve the growth, gonadal development, and health of female Pengze crucian carp. In this study, the effect of 35.73% protein concentration was better than in the other two groups.

Cross-linked g-C3N4 nanofibers enable thermal stable composite membranes for high-performance loose nanofiltration - Wan-Ting Lin; Ping Fu; Wan-Long Li; Yuan-Hui Yu; Zi-Lu Zhang; Hong-Yu Fan; Xiao-Jun Huang; Zhi-Kang Xu; Ling-Shu Wan (Chemical Engineering Journal, 2024)

Derivatives of Br-doped metal-organic framework for improved acetaldehyde adsorption-photocatalytic oxidation - Jun Wang; Changqing Yang; Mingli Fu; Daiqi Ye; Lan Fan; Yun Hu (Science of The Total Environment, 2024)

Reproducing surface water isoscapes of δ18O and δ2H across China: A machine learning approach - Huawu Wu; Hongxiang Fan; Jing Li; Fu-Jun Yue; Ergang Lian; Congsheng Fu; Ruiyu Lei; Mengyao Ding; Jinzhao Liu; Xiao-Yan Li (Journal of Hydrology, 2024)

Pearl-inspired self-extinguishing, thermal-conductive, and robust thermoplastic polyurethane composite by strengthening inter-layer packing - Yongbin Wang; Kaichao Pan; Yong Fan; Yifeng Fu; Jieying Tu; Weiqiang Zhao; Wenjin Guo; Zunfeng Liu; Jun Qiu (Chemical Engineering Journal, 2024)

Flow prediction of heterogeneous nanoporous media based on physical information neural network - Liang Zhou; Hai Sun; Dongyan Fan; Lei Zhang; Gloire Imani; Shuaishi Fu; Yongfei Yang; Kai Zhang; Jun Yao (Gas Science and Engineering, 2024)

Effect of low temperatures on fracture properties of steel fibre reinforced rubberised concrete - Jun Su; Ziyang Xu; Songbo Wang; Farun Shui; Fu Huang; Haixin Yang; Qingdian Zeng; Zikang Fan (Journal of Cleaner Production, 2024)

Genetic architecture of ecological divergence between Oryza rufipogon and Oryza nivara - Qing‐Lin Meng; Cheng‐Gen Qiang; Ji‐Long Li; Mu‐Fan Geng; Ning‐Ning Ren; Zhe Cai; Mei‐Xia Wang; Zi‐Hui Jiao; Fu‐Min Zhang; Xian‐Jun Song; Song Ge (Molecular Ecology, 2024)
Ecological divergence due to habitat difference plays a prominent role in the formation of new species, but the genetic architecture during ecological speciation and the mechanism underlying phenotypic divergence remain less understood. Two wild ancestors of rice ( Oryza rufipogon and Oryza nivara ) are a progenitor‐derivative species pair with ecological divergence and provide a unique system for studying ecological adaptation/speciation. Here, we constructed a high‐resolution linkage map and conducted a quantitative trait locus (QTL) analysis of 19 phenotypic traits using an F 2 population generated from a cross between the two Oryza species. We identified 113 QTLs associated with interspecific divergence of 16 quantitative traits, with effect sizes ranging from 1.61% to 34.1% in terms of the percentage of variation explained (PVE). The distribution of effect sizes of QTLs followed a negative exponential, suggesting that a few genes of large effect and many genes of small effect were responsible for the phenotypic divergence. We observed 18 clusters of QTLs (QTL hotspots) on 11 chromosomes, significantly more than that expected by chance, demonstrating the importance of coinheritance of loci/genes in ecological adaptation/speciation. Analysis of effect direction and v ‐test statistics revealed that interspecific differentiation of most traits was driven by divergent natural selection, supporting the argument that ecological adaptation/speciation would proceed rapidly under coordinated selection on multiple traits. Our findings provide new insights into the understanding of genetic architecture of ecological adaptation and speciation in plants and help effective manipulation of specific genes or gene cluster in rice breeding.

Differential metabolites screening in yak (Bos grunniens) seminal plasma after cryopreservation and the evaluation of the effect of galactose on post-thaw sperm motility - Yilin Fan; Xiaowei Li; Jian Li; Xianrong Xiong; Shi Yin; Wei Fu; Peng Wang; Jun Liu; Yan Xiong (Theriogenology, 2024)

Hierarchically ordered microporous Ag2S QDs-CoOx/NC nanostructures for enhancing photocatalytic CO2 reduction to chemical fuels - Shengpeng Mo; Lili Huang; Xin Zhao; Jun Li; Xuegang Ding; Xiaobin Zhou; Yanan Zhang; Yinming Fan; Mingming Fu; Hongxiang Zhu; Qinglin Xie; Daiqi Ye (Fuel, 2024)

Dissecting ZnOX/Cu interfacial self-encapsulation and methanol-induced strong metal-support interaction of the highly active alloyed CuZn and ZnO for methanol steam reforming - Aixia Wang; Peng Fu; Qingwen Fan; Yi Wang; Liang Zheng; Song Hu; Jun Xiang; Chaoyun Song (Fuel, 2024)

Manganese doped hollow cobalt oxide catalysts for highly efficient oxygen evolution in wide pH range - Jing-Yi Xie; Fu-Li Wang; Xue-Jun Zhai; Xin Li; Yu-Sheng Zhang; Ruo-Yao Fan; Ren-Qing Lv; Yong-Ming Chai; Bin Dong (Chemical Engineering Journal, 2024)

Lubricating MXenzyme-based hybrid hydrogel reverses oxidative damage to alleviate osteoarthritis - Zhao Zhang; Debin Cheng; Jingxin Pan; Dong Liu; Jun Fu; Hongbin Fan (Chemical Engineering Journal, 2024)

Changes in soil microbial community and co-occurrence network after long-term no-tillage and mulching in dryland farming - Zijun Dai; Jun Fan; Wei Fu; Xiaotao Niu; Qian Yang; Mingde Hao (Plant and Soil, 2024)

Effects of tillage practices on soil organic carbon, microbial community and necromass in a double rice cropping system - Jian-Ying Qi; Xiang-Bin Yao; Xue-Chan Zhang; Mei-Yi Fan; Jian-Fu Xue; Jun-Li Cao; Ahmad Latif Virk; Sheng-Gang Pan; Xiang-Ru Tang (Applied Soil Ecology, 2024)

Petrogenesis and tectonic implications of the Silurian adakitic granitoids in the eastern segment of the Qilian Orogenic Belt, Northwest China - Jiao-Long Zhao; Xiao-Jun Huang; Pei-Qing Hu; Zhen-Xi Yang; Ying Fan; Er-Teng Wang; Fu-Bo Yang; Jing-Yu Zhang (Acta Geochimica, 2024)

Identification and analysis of microplastics in human lower limb joints - Zhuo Li; Yifan Zheng; Zulipikaer Maimaiti; Jun Fu; Fan Yang; Zhi-Yuan Li; Yanli Shi; Li-Bo Hao; Ji-Ying Chen; Chi Xu (Journal of Hazardous Materials, 2024)

Effects of sucrose esters on whipping capabilities of aerated emulsions - Pengkai Xie; Jun Jin; Hua Xu; Daohai Wang; Shiqi Fu; Qinyuan Fan; Ziwei Gao; Yuhang Chen; Qingzhe Jin; Xingguo Wang (Food Hydrocolloids, 2023)

Evolution law and mechanism of time-delayed spalling in a deep TBM tunnel: A case study - Chen Fan; Xia-Ting Feng; Lianjie Fu; Jun Zhao; Chengxiang Yang; Zhibin Yao; Jun Wang; Fei Wei (Engineering Geology, 2023)

Gastrointestinal digestion fates of lipids based on pH-stat and Caco-2 cells models: Superior bioavailability of triglyceride monomer derived from silkworm pupae oil - Cheng-Hai Yan; Xiao-Meng Xun; Richard A. Herman; Yu-Fan Zhan; Lu-Chan Gong; Fu-An Wu; Jun Wang (Food Bioscience, 2023)

Hollow cavity engineering of MOFs-derived hierarchical MnOx structure for highly efficient photothermal degradation of ethyl acetate under light irradiation - Jun Li; Shengpeng Mo; Xuegang Ding; Lili Huang; Xiaobin Zhou; Yinming Fan; Yanan Zhang; Mingming Fu; Qinglin Xie; Daiqi Ye (Chemical Engineering Journal, 2023)

Different reoxygenation rates induce different metabolic, apoptotic and immune responses in Golden Pompano (Trachinotus blochii) after hypoxic stress - Tian Jiang; Ye Song Liang; Yue Gu; Fu Cheng Yao; Yi Fan Liu; Kai Xi Zhang; Fei Biao Song; Jun Long Sun; Jian Luo (Fish & Shellfish Immunology, 2023)

Effects of organic carbon sources on algal biofilm formation and insight into mechanism - Jun Qian; Siyi Fu; Jingjing Li; Tatsuki Toda; Hongwu Li; Mutsumi Sekine; Yoshiki Takayama; Shinichi Koga; Shengxi Shao; Liangliang Fan; Peilun Xu; Xiru Zhang; et al. (Algal Research, 2023)

Surprising leopard restoration in fragmented ecosystems reveals connections as the secret to conservation success - Fu Yanwen; Zhao Guojing; Dai Wenqian; Wang Yue; Li Jiawei; Tan Mengyu; Li Yan; Liu Haoran; Xie Bing; Jin Xiao; Fan Enyu; Zhao Lulu; et al. (Science of The Total Environment, 2023)

Numerical study of the influence of loading rate on fracture mechanism in elastoplastic rock-like materials with a modified phase-field model - Shi-Fan Liu; Wei Wang; Ya-Jun Cao; Hai-Feng Li; Jian-Fu Shao (International Journal of Rock Mechanics and Mining Sciences, 2023)

Hypoxia alters glucose and lipid metabolisms in golden pompano (Trachinotus blochii) - Tian Jiang; Jun Long Sun; Yue Gu; Fu Cheng Yao; Ye Song Liang; Yi Fan Liu; Kai Xi Zhang; Fei Biao Song; Li Zhou; Zhong Wei Wang; Jian Fang Gui; Jian Luo (Aquaculture, 2023)

Soil microbial communities and their co-occurrence networks in response to long-term Pb–Zn contaminated soil in southern China - Hongyang Xu; Bingqing Fu; Jiaqi Lei; Hui Kang; Jun Wang; Xinhao Huang; Fan Zhu (Environmental Science and Pollution Research, 2022)

Four sesquiterpenoids from the vegetable raw material Schisandra chinensis (Turcz.) Baill.: leaves and stems - Yong-Cheng Yang; Lu-Qi Liu; Kun-Jun Wang; Xue-Qing Zhang; San-Peng Fan; Xiao-Xu Gao; An-Hua Wang; Jing-Ming Jia; Chun-Wang Fu (Natural Product Research, 2022)

The recombinant subunit vaccine encapsulated by alginate‐chitosan microsphere enhances the immune effect against Micropterus salmoides rhabdovirus - Fei‐Fan Xu; Fu‐Yi Jiang; Guo‐Qing Zhou; Jun‐Yao Xia; Fei Yang; Bin Zhu (Journal of Fish Diseases, 2022)
The disease caused by Micropterus salmoides rhabdovirus (MSRV) has brought substantial economic losses to the largemouth bass aquaculture industry in China. Vaccination was considered as a potential way to prevent and control this disease. As a kind of sustained and controlled release system, alginate and chitosan microspheres (SA‐CS) are widely used in the development of oral vaccination for fish. Here, we prepared a king of alginate‐chitosan composite microsphere to encapsulate the second segment of MSRV glycoprotein (G2 protein) and then evaluated the immune effect of the microsphere vaccine on largemouth bass. Largemouth bass were vaccinated via intragastric immunization by different treatments (PBS, SA‐CS, G2 and SA‐CS‐G2). The results showed that a stronger immune response including serum antibody levels, immune‐related physiological indexes (acid phosphatase, alkaline phosphatase, superoxide dismutase and total antioxidant capacity) and the expression of immune‐related gene ( IgM、IL‐8、IL‐1β、CD4、TGF‐β、TNF‐α ) can be induced obviously with SA‐CS‐G2 groups compared with G2 groups when fish were vaccinated. Furthermore, fish were injected with a lethal dose of MSRV after immunization for 28 days, and the highest relative percentage survival (54.8%) was observed in SA‐CS‐G2 group (40 μg per fish), which is significantly higher than that of G2 group (25.8%). This study showed that alginate‐chitosan microspheres as the vaccine carrier can effectively improve the immune effect of oral vaccination and induce better immune protection effect against MSRV infection.

Evaluation of LAI Estimation of Mangrove Communities Using DLR and ELR Algorithms With UAV, Hyperspectral, and SAR Images - Bolin Fu; Jun Sun; Yeqiao Wang; Wenlan Yang; Hongchang He; Lilong Liu; Liangke Huang; Donglin Fan; Ertao Gao (Frontiers in Marine Science, 2022)
The high-precision estimation of mangrove leaf area index (LAI) using a deep learning regression algorithm (DLR) always requires a large amount of training sample data. However, it is difficult for LAI field measurements to collect a sufficient amount of sample data in mangrove wetlands. To tackle this challenge, this paper proposed an approach for expanding training samples and quantitatively evaluated the performance of estimating LAI for mangrove communities using Deep Neural Networks (DNN) and Transformer algorithms. This study also explored the effects of unmanned aerial vehicle (UAV) and Sentinel-2A multispectral, orbital hyper spectral (OHS), and GF-3 SAR images on LAI estimation of different mangrove communities. Finally, this paper evaluated the LAI estimation ability of mangrove communities using ensemble learning regression (ELR) and DLR algorithms. The results showed that: (1) the UAV images achieved the better LAI estimation of different mangrove communities (R 2 = 0.5974–0.6186), and GF-3 SAR images were better for LAI estimation of Avicennia marina with high coverage (R 2 = 0.567). The optimal spectral range for estimating LAI for mangroves in the optical images was between 650–680 nm. (2) The ELR model outperformed single base model, and produced the high-accuracy LAI estimation (R 2 = 0.5266–0.713) for different mangrove communities. (3) The average accuracy (R 2 ) of the ELR model was higher by 0.0019–0.149 than the DLR models, which demonstrated that the ELR model had a better capability (R 2 = 0.5865–0.6416) in LAI estimation. The Transformer-based LAI estimation of A. marina (R 2 = 0.6355) was better than the DNN model, while the DNN model produced higher accuracy for Kandelia candel (KC) (R 2 = 0.5577). (4) With the increase in the expansion ratio of the training sample (10–50%), the LAI estimation accuracy (R 2 ) of DNN and Transformer models for different mangrove communities increased by 0.1166–0.2037 and 0.1037–0.1644, respectively. Under the same estimation accuracy, the sample enhancement method in this paper could reduce the number of filed measurements by 20–40%.

Astragalus Polysaccharides Reduce High-glucose-induced Rat Aortic Endothelial Cell Senescence and Inflammasome Activation by Modulating the Mitochondrial Na+/Ca2+ Exchanger - Xin-Yu Miao; Xiao-Xiao Zhu; Zhao-Yan Gu; Bo Fu; Shao-Yuan Cui; Yuan Zu; Ling-Jun Rong; Fan Hu; Xiang-Mei Chen; Yan-Ping Gong; Chun-Lin Li (Cell Biochemistry and Biophysics, 2022)

Experimental Study on the Disintegration Properties of Red Sandstone - Bao-Jie Fan; Fu-jun Zhao; Zong-tang Zhang; Yong-hong Liu (Geotechnical and Geological Engineering, 2022)

Infestation and distribution of mites on the Yunnan red-backed vole (Eothenomys miletus) in Yunnan Province of southwest China between 2001 and 2015 - Rong Xiang; Xian-Guo Guo; Tian-Guang Ren; Cheng-Fu Zhao; Rong Fan; Zhi-Wei Zhang; Ke-Yu Mao; Pei-Ying Peng; Xiao-Bin Huang; Ti-Jun Qian (Biologia, 2022)

Cryostructures and ground ice content in ice-rich permafrost area of the Qinghai-Tibet Plateau with Computed Tomography Scanning - Xing-wen Fan; Zhan-ju Lin; Ze-yong Gao; Xiang-lian Meng; Fu-jun Niu; Jing Luo; Guo-an Yin; Fu-jun Zhou; Ai-yu Lan (Journal of Mountain Science, 2021)

Soil particle-size distribution and aggregate stability of new reconstructed purple soil affected by soil erosion in overland flow - Feng-Lin Zuo; Xiao-Yan Li; Xiao-Fan Yang; Yang Wang; Yu-Jun Ma; Yu-Han Huang; Chao-Fu Wei (Journal of Soils and Sediments, 2020)

GPS satellite inter-frequency clock bias estimation using triple-frequency raw observations - Lei Fan; Chuang Shi; Min Li; Cheng Wang; Fu Zheng; Guifei Jing; Jun Zhang (Journal of Geodesy, 2019)

Microfluidic tools for lipid production and modification: a review - Jin-Zheng Wang; Lin-Lin Zhu; Fan Zhang; Richard Ansah Herman; Wen-Jing Li; Xue-Jiao Zhou; Fu-An Wu; Jun Wang (Environmental Science and Pollution Research, 2019)

Two-factor ANOVA of SSH and RNA-seq analysis reveal development-associated Pi-starvation genes in oilseed rape - Zhong-Wei Zhang; Ling-Yang Feng; Jian-Hui Wang; Yu-Fan Fu; Xin Cai; Chang-Quan Wang; Jun-Bo Du; Ming Yuan; Yang-Er Chen; Pei-Zhou Xu; Ting Lan; Guang-Deng Chen; et al. (Planta, 2019)

Haploid plant regeneration from hardy kiwifruit (Actinidia arguta Planch.) anther culture - Guang-Fu Wang; Hong-Yan Qin; Dan Sun; Shu-Tian Fan; Yi-Ming Yang; Zhen-Xing Wang; Pei-Llei Xu; Ying Zhao; Ying-Xue Liu; Jun Ai (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Expression-based genotyping of the rice blast resistance genes in the elite maintainer line Yixiang1B - Li Wang; Xiao-Hong Hu; Gang Lin; De-Ming Zhao; Jun Shi; Zhi-Xue Zhao; Rui Zeng; Heng-Jing Li; De-Qiang Li; Jing Fan; Yan Li; Fu Huang; et al. (European Journal of Plant Pathology, 2017)

Enhanced Therapeutic Potential of Nano-Curcumin Against Subarachnoid Hemorrhage-Induced Blood–Brain Barrier Disruption Through Inhibition of Inflammatory Response and Oxidative Stress - Zong-yong Zhang; Ming Jiang; Jie Fang; Ming-feng Yang; Shuai Zhang; Yan-xin Yin; Da-wei Li; Lei-lei Mao; Xiao-yan Fu; Ya-jun Hou; Xiao-ting Fu; Cun-dong Fan; et al. (Molecular Neurobiology, 2017)

Characterization, promoter analysis and expression of the interleukin-6 gene in blunt snout bream, Megalobrama amblycephala - Xiaoqin Fu; Zhujin Ding; Jun Fan; Huanling Wang; Fengjuan Zhou; Lei Cui; Chen Boxiang; Weimin Wang; Hong Liu (Fish Physiology and Biochemistry, 2016)

The heterogeneity of islet autoantibodies and the progression of islet failure in type 1 diabetic patients - Jin Liu; Lingling Bian; Li Ji; Yang Chen; Heng Chen; Yong Gu; Bingqin Ma; Wei Gu; Xinyu Xu; Yun Shi; Jian Wang; Dalong Zhu; et al. (Science China Life Sciences, 2016)

DSePA Antagonizes High Glucose-Induced Neurotoxicity: Evidences for DNA Damage-Mediated p53 Phosphorylation and MAPKs and AKT Pathways - Kun Wang; Xiao-yan Fu; Xiao-ting Fu; Ya-jun Hou; Jie Fang; Shuai Zhang; Ming-feng Yang; Da-wei Li; Lei-lei Mao; Jing-yi Sun; Hui Yuan; Xiao-yi Yang; et al. (Molecular Neurobiology, 2016)

Gabapentinoid Insensitivity after Repeated Administration is Associated with Down-Regulation of the α2δ-1 Subunit in Rats with Central Post-Stroke Pain Hypersensitivity - Yan Yang; Fei Yang; Fan Yang; Chun-Li Li; Yan Wang; Zhen Li; Yun-Fei Lu; Yao-Qing Yu; Han Fu; Ting He; Wei Sun; Rui-Rui Wang; et al. (Neuroscience Bulletin, 2016)

Isolation and characterization of a crude oil degrading bacteria from formation water: comparative genomic analysis of environmental Ochrobactrum intermedium isolate versus clinical strains - Lu-jun Chai; Xia-wei Jiang; Fan Zhang; Bei-wen Zheng; Fu-chang Shu; Zheng-liang Wang; Qing-feng Cui; Han-ping Dong; Zhong-zhi Zhang; Du-jie Hou; Yue-hui She (Journal of Zhejiang University-SCIENCE B, 2015)

Identification of Two Cucumber Putative Silicon Transporter Genes in Cucumis sativus - Hua-Sen Wang; Chao Yu; Pei-Pei Fan; Bin-Fu Bao; Tao Li; Zhu-Jun Zhu (Journal of Plant Growth Regulation, 2015)

Paracercospora dictamnicola sp. nov. from China - Yang-Hui Ou; Ru-Jun Zhou; Jun-Fan Fu; Yue Yuan; Hai-Jiao Xu (Mycological Progress, 2015)

mTOR ATP-competitive inhibitor INK128 inhibits neuroblastoma growth via blocking mTORC signaling - Huiyuan Zhang; Jun Dou; Yang Yu; Yanling Zhao; Yihui Fan; Jin Cheng; Xin Xu; Wei Liu; Shan Guan; Zhenghu Chen; Yan shi; Roma Patel; et al. (Apoptosis, 2015)

Post-stroke pain hypersensitivity induced by experimental thalamic hemorrhage in rats is region-specific and demonstrates limited efficacy of gabapentin - Fei Yang; Han Fu; Yun-Fei Lu; Xiao-Liang Wang; Yan Yang; Fan Yang; Yao-Qing Yu; Wei Sun; Jia-Shuang Wang; Michael Costigan; Jun Chen (Neuroscience Bulletin, 2014)

MiR-15a-16 represses Cripto and inhibits NSCLC cell progression - Feng Chen; Shi-ke Hou; Hao-jun Fan; Ying-fu Liu (Molecular and Cellular Biochemistry, 2014)

Streptomycin inhibits electrophysiological changes induced by stretching of chronically infarcted rat hearts - Jun-xian Cao; Lu Fu; Qian-ping Gao; Rong-sheng Xie; Fan Qu (Journal of Zhejiang University-SCIENCE B, 2014)

Prevalence of human papillomavirus infection in esophageal and cervical cancers in the high incidence area for the two diseases from 2007 to 2009 in Linzhou of Henan Province, Northern China - Hong Yan Liu; Sheng Li Zhou; Jian Wei Ku; Dong Yun Zhang; Bei Li; Xue Na Han; Zong Min Fan; Ji Li Cui; Hong Li Lin; Er Tao Guo; Xi Chen; Yuan Yuan; et al. (Archives of Virology, 2014)

A novel finding for enterovirus virulence from the capsid protein VP1 of EV71 circulating in mainland China - Yongjuan Liu; Chong Fu; Suying Wu; Xiong Chen; Yingying Shi; Bingfei Zhou; Lianglu Zhang; Fengfeng Zhang; Zhihao Wang; Yingying Zhang; Chengpeng Fan; Song Han; et al. (Virus Genes, 2014)

Occurrence of rust of Sophora flavescens caused by Uromyces sophorae-flavescentis in China - Ru-Jun Zhou; Jun-Fan Fu; Ning Hao; Zhen Liu; Ying Sun (Phytoparasitica, 2013)

T-2 Toxin Contamination in Grains and Selenium Concentration in Drinking Water and Grains in Kaschin–Beck Disease Endemic Areas of Qinghai Province - Li-Yan Sun; Qiang Li; Fan-Gang Meng; Ying Fu; Zhi-Jun Zhao; Li-Hua Wang (Biological Trace Element Research, 2012)

A high-frequency cyclic secondary somatic embryogenesis system for Cyclamen persicum Mill - Cui Rong You; Ting Jun Fan; Xue Qin Gong; Fu Hua Bian; Li Kun Liang; Fu Ning Qu (Plant Cell, Tissue and Organ Culture (PCTOC), 2011)

A novel human derived cell-penetrating peptide in drug delivery - Jian Zhao; Peng Gao; Wei Xiao; Li-Qiang Fan; Fu-Jun Wang; Su-Xia Li; Jian-Wen Liu (Molecular Biology Reports, 2011)

Differential expression of expressed sequence tags in alfalfa roots under aluminum stress - Fu Fan; Xin-Wei Li; Yue-Ming Wu; Zhuo-Sheng Xia; Jin-Jun Li; Wen Zhu; Jin-Xin Liu (Acta Physiologiae Plantarum, 2011)

Induced apoptotic action of recombinant trichosanthin in human stomach adenocarcinoma MCG803 cells - Jun Xu; De-Fu Gao; Guo-Li Yan; Jian-Ming Fan (Molecular Biology Reports, 2009)

Inhibition on Hepatitis B virus in vitro of recombinant MAP30 from bitter melon - Jian Ming Fan; Qiao Zhang; Jun Xu; Sha Zhu; Tao Ke; De Fu Gao; Yu Bao Xu (Molecular Biology Reports, 2009)